High-k hafnium oxide based thin films using laser molecular beam epitaxy for gate dielectrics - Lu, Yuekang (2008)
The constant increase in integrated circuit densities predicted by Moore’s law requires the continuous reduction of the CMOS device dimensions such as the gate length, gate oxide thickness, etc. Silicon dioxide (SiO2) has been used as the gate oxide and been aggressively scaled for more than 30 years. Nowadays in the state-of-the-art MOSFET, the gate oxide thickness is reduced to 1.2 nm. However, with the use of such thin SiO2,direct tunneling dominates the dielectric conduction which results in high leakage current and unacceptable power dissipations. In order to maintain the performance improvement trends, there are growing interests in the replacement of SiO2 with a high-k dielectric material.